Algorithm 758: VLUGR2 a vectorizable adaptive-grid solver for PDEs in 2D. - Blom, J. G.; Trompert, R. A.; Verwer, J. G.
This article deals with an adaptive-grid finite-difference solver for time-dependent two-dimensional systems of partial differential equations. It describes the ANSI Fortran 77 code, VLUGR2, autovectorizable on the Cray Y-MP, that is based on this method. The robustness and the efficiency of the solver, both for vector and scalar processors, are illustrated by the application of the code to two example problems arising from a groundwater-flow model.
Keywords: Adaptive-grid methods; Iterative solvers; Method of lines; Nonsymmetric sparse linear systems; Partial different equations; Software; Vectorization